Documents from F. Taylor Ostrander at Oxford, John R. Commons' Reasonable value and Clarence E. Ayres' last course - Commons, John R. 1862-1945; Ayres, Clarence Edwin, 1891-1972; Ostrander, F. Taylor; Samuels, Warren J., 1933- (Emerald, 2008)
Volume 26B continues, in part, the important graduate career of F.Taylor Ostrander, notable the year spent at Oxford University. Among his tutors and professors were some of the leading faculty at Oxford. The volume also contains two documents important for the history of Instituitional Economics, John R. Commons' Reasonable Value, his first effort leading to his Institutional Economics; and notes from Clarence E. Ayres' final course taught on institutional economics, at the University of Texas.
Keywords: Business & Economics -- General.; Economic theory & philosophy.; Economic history.; Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books